(untitled) (Journal of Governance and Development (JGD), 2024)
The effects of certain governance indicators on economic growth in an African country (Nigeria) have been researched in this study. Governance indicators such as institutional quality, and rule of law are analysed to understand their effect and direction on economic growth. The data are from the World Development and Governance Indicators (WDI & WGI) and cover the years 1996 to 2016. Using the autoregressive distributed lag (ARDL) approach to estimate the relationship, we discovered that the coefficient of governance indicators produces mixed results, even though the index of governance has a negative influence on economic growth. Furthermore, uni-directional causality was evident between certain governance indicators and trade openness. Significant policy implications suggested by the findings include the government of this African country should put in more effort into improving the general governance structure toward stability. Hence, this will lead to increased investor confidence in the countries’ economies.